MXene composite material for supercapacitor and preparation method of MXene composite material

By compounding the alkalized MXene with Prussian Blue and expanding the layer spacing through in-situ growth method, the problem of insufficient performance of MXene material is solved, and a supercapacitor electrode material with high specific capacitance, excellent rate performance and cycling stability is achieved.

CN119742183AActive Publication Date: 2025-04-01CHANGZHOU UNIV

Patent Information

Application Number
CN202411938534.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Existing supercapacitor electrode materials have shortcomings in cyclic stability and energy density, especially the self-stacking effect of MXene materials affects its performance.

Method used

The one-step reaction method is used to compound the alkalized MXene with Prussian blue, and the Prussian blue is grown between the layers and the surface of the MXene through the in-situ growth method, expanding the layer spacing and improving electrochemical performance.

Benefits of technology

It improves the specific capacitance, rate performance and cycle stability of MXene composite materials, while simplifying the process and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742183A_ABST
    Figure CN119742183A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of supercapacitor electrode materials, in particular to an MXene composite material for a supercapacitor and a preparation method of the MXene composite material. The preparation method comprises the following steps: preparing an MXene nanosheet; the MXene nanosheet is put into a NaOH solution for alkali treatment; and mixing and stirring the alkalized MXene nanosheet, CuSO4. 5H2O and K3Fe (CN) 6, carrying out centrifugal washing, and drying in a vacuum drying oven to finally obtain the MXene composite material. The MXene is subjected to alkali treatment to enlarge the interlayer spacing of the MXene, and the MXene is compounded with the Prussian blue, so that the Prussian blue grows between the MXene layers and on the surface of the MXene, the interlayer spacing of the MXene is further enlarged, self-stacking of the MXene is inhibited, the conductivity of the Prussian blue is improved, and the electrochemical performance of the MXene-based supercapacitor electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitor electrode materials, and in particular to a MXene composite material for a supercapacitor and a preparation method thereof. Background Art

[0002] Supercapacitors have attracted widespread attention due to their high output power, fast charge and discharge capabilities, wide operating temperature range, and ultra-long cycle. The core of supercapacitors lies in their electrode materials. Currently, common electrode materials include carbon-based materials, metal oxides, conductive polymers, and emerging MXene materials. The performance of these materials directly determines the energy density, power density, and cycle stability of supercapacitors.

[0003] Carbon-based materials (such as activated carbon, graphene, and carbon nanotubes) have high specific surface area, low cost, and good conductivity. Their capacitance mainly comes from double-layer capacitance and lacks obvious Faraday reaction activity, resulting in low energy density.

[0004] Metal oxides (such as MnO2, RuO2, NiO) provide high Faradaic capacitance through reversible redox reactions, but their high cost (such as RuO2) and low cycle life (such as MnO2) limit their widespread application. In addition, some metal oxides have poor conductivity and need to be compounded with other conductive materials.

[0005] Conductive polymers such as polyaniline (PANI) and polypyrrole (PPy) have good electrochemical activity and flexibility, but their cycle life is short and the polymers are easily degraded during repeated redox processes.

[0006] MXene materials are a class of transition metal carbon / nitrogen / carbon nitrides with a two-dimensional layered structure, which have high conductivity and excellent electrochemical properties, but their self-stacking effect affects the performance. Introducing a rigid framework into MXene sheets is a useful measure to expand the interlayer spacing and accelerate ion transport. Prussian blue has an open framework structure and abundant redox active sites, but its cycle life is unstable and its reversible capacity is low.

[0007] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0008] The technical problem to be solved by the present invention is: to provide a MXene composite material for supercapacitors and a preparation method thereof, wherein the alkalized MXene is compounded with Prussian blue by a one-step reaction method, and by placing the raw materials together in a MXene monolayer dispersion, a larger Prussian blue nanoparticle can be generated in situ in a short time, thereby increasing the loading amount of Prussian blue on MXene compared with a step-by-step reaction.

[0009] The present invention uses an in-situ growth method to stir and compound the alkalized MXene and Prussian blue at room temperature, so that the Prussian blue grows between the MXene layers and on the surface, expands the interlayer distance of the MXene, improves its electrochemical performance, and has the advantages of simple and safe process.

[0010] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing a MXene composite material for a supercapacitor comprises the following steps: S01: Preparation of MXene nanosheets: deionized water and HCl are stirred and mixed to obtain a mixed acid solution; LiF and Ti3AlC2 powders are slowly added to the mixed acid solution in sequence and stirred evenly, and then transferred to an oil bath for heating and stirring etching; after the etching is completed, the precipitate is centrifugally washed with HCl and deionized water in sequence until the pH of the supernatant is neutral; the precipitate is placed in an ultrasonic crusher and ultrasonicated with protective gas, and then placed in a centrifuge for centrifugation to obtain the upper suspension and place it in a cold dryer for cold drying; In a mixed acid solution of HCl and deionized water, LiF reacts with HCl to produce HF, which then selectively etches the Al layer in Ti3AlC2. After a long period of oil bath stirring and heating, the Al atoms are completely removed, exposing the two-dimensional layer structure of MXene (Ti3C2). After etching, ultrasonic treatment can be used to further peel off the MXene nanosheets, and a protective gas (such as argon) is introduced to avoid the formation of TiO2 on the surface of the Ti3C2 layer due to oxidation, ultimately forming evenly dispersed MXene nanosheets.

[0011] Preferably, in step S01, in the mixed acid solution, the volume ratio of deionized water to HCl is 1:2.9-3.1, which can ensure that the acid concentration is moderate, which is conducive to the generation of HF and avoids the influence of too strong or too weak acidic environment on the etching process; the mass ratio of LiF to Ti3AlC2 is 1:1-1.2, and the optimized ratio of LiF can ensure that sufficient HF is generated during the etching process to fully react with the Al layer to achieve efficient etching, while avoiding excessive HF causing material waste or corrosion to the equipment.

[0012] Preferably, in step S01, when the oil bath is transferred to the oil bath for heating, stirring and etching, the heating time of the oil bath is 48 to 52 hours. The Al layer of Ti3AlC2 requires a long time and acid etching at an appropriate temperature to be completely removed. The heating time of 48 to 52 hours can ensure that the Al layer reacts fully, avoids incomplete reaction leading to insufficient etching, generation of impurities or incompletely stripped products, ensures that the final generated MXene has high purity, and reduces the amount of incompletely etched Ti3AlC2 residue. The heating temperature of the oil bath is 38-42°C. Etching at a lower temperature allows the functional groups on the surface of the MXene to be generated more stably, avoiding oxidation or excessive stripping of the layers due to intense reactions at high temperatures. Preferably, in step S01, the precipitate obtained after etching is first centrifugally washed twice with HCl, and then centrifugally washed with deionized water until the pH of the supernatant is neutral; using HCl to centrifugally wash twice can effectively dissolve and remove most of the reaction by-products, ensuring the purity of MXene in the precipitate, and then washing with deionized water until the pH of the supernatant is neutral, which can further remove excess acidic substances (HCl and HF) to avoid damage to the MXene layer structure and interference with subsequent ultrasonic treatment and composite reaction steps.

[0013] Preferably, the volume of HCl washing is 3-5 mL, which can ensure complete washing while avoiding excessive consumption of functional groups on the surface of MXene due to excessive acid, thereby retaining active groups on the surface of the material.

[0014] Preferably, the centrifugal speed is 3000-4000 rpm; the centrifugal time is 3-5 min; reasonable centrifugal speed and time make the separation of precipitation and liquid phase more thorough, avoiding the metal ions (such as Al 3+ ) and other impurities are re-adsorbed onto the MXene surface.

[0015] Preferably, the speed of centrifugation with deionized water is 3500-6000 rpm, the centrifugation time is 4-6 min, and the number of centrifugation is 7-10 times, so as to ensure a more thorough separation of precipitation and liquid phase, avoid repeated residual impurities, and prevent damage to the sheet structure due to excessive centrifugal force.

[0016] Preferably, in step S01, the precipitate is placed in an ultrasonic crusher and ultrasonicated with protective gas for 2 to 2.5 hours, and then placed in a centrifuge. After centrifugation at 3500 to 4000 rpm for 40 to 50 minutes, ensure that the unpeeled heavier layers (thick layers or impurities) settle to the bottom; the thin layer or single layer of MXene flakes is retained in the upper layer in the form of a suspension to improve purity and dispersibility. The upper layer suspension is placed in a cold dryer for cold drying, which avoids the capillary force between the flakes caused by water evaporation during the traditional heating and drying process, thereby effectively preventing the flakes from agglomerating and collapsing, and maintaining the two-dimensional flake structure of MXene.

[0017] S02: Place the MXene nanosheets in a NaOH solution, stir and heat in an oil bath, centrifuge and wash, and then dry in a vacuum drying oven; When MXene nanosheets are placed in a NaOH solution, NaOH reacts with the functional groups on the surface of MXene (such as F - , -OH, etc.) to promote surface activation and functionalization. This process will remove some of the fluorine (F - ), and increase the surface hydroxyl group (-OH), thereby improving the binding ability of MXene with subsequent Prussian blue. The surface functional groups of the alkalized MXene are rich, which enhances its hydrophilicity and chemical activity. This surface modification helps the uniform deposition and tight binding of Prussian blue, thereby improving the structural stability and electrochemical properties of the composite material.

[0018] Preferably, in step S02, the concentration of the NaOH solution is 0.9-1.2 mol / l; a moderate NaOH concentration can effectively remove residual fluoride on the surface and introduce more hydroxyl groups (-OH) to achieve surface functionalization. Too low a NaOH concentration will result in incomplete alkalization and affect material properties; too high a concentration may cause damage to the sheet or chemical corrosion.

[0019] Preferably, the temperature of the oil bath is 60-80°C and the heating time is 1-1.5 hours, which can fully achieve alkalization without destroying the two-dimensional layer structure of MXene and avoiding deformation or breakage of the layer.

[0020] Preferably, in step S02, the washing speed is 5000-6000 rpm, the centrifugation time is 3-5 min, and the number of centrifugations is 7-10 times; the drying temperature is 40-60 ° C, and the drying time is 10-12 hours. High speed combined with short time helps to quickly separate the MXene sheets from impurities in the solution. Higher speed increases the centrifugal force, causing unreacted NaOH, reaction byproducts (such as NaF), and other soluble impurities to sink quickly, ensuring a more thorough separation, ensuring that the solute concentration in the centrifugal supernatant gradually decreases, and finally achieving a solution close to neutrality. Drying in a moderate low temperature environment reduces the risk of surface oxidation when the sheets are exposed to high temperature air, thereby maintaining the high conductivity of MXene.

[0021] S03: The alkalized MXene nanosheets are mixed with CuSO4·5H2O and K3Fe(CN)6, stirred, centrifuged and washed, and dried in a vacuum drying oven to obtain a MXene / Prussian blue composite material.

[0022] In the mixed solution of CuSO4 and K3Fe(CN)6, Cu 2+ and [Fe(CN)6] 3- The reaction occurs to generate Prussian blue (KFe[Fe(CN)6]). The alkalinized MXene surface contains abundant hydroxyl (-OH) and carboxyl (-COOH) groups, which can serve as active sites for the deposition of Prussian blue, allowing Prussian blue to be evenly loaded on the surface of MXene. At the same time, the two-dimensional layered structure of MXene provides a carrier with high conductivity and high specific surface area for Prussian blue.

[0023] Preferably, in step S03, the molar ratio of CuSO4·5H2O and K3Fe(CN)6 is 2:1, which can generate a stable Prussian blue compound (KFe[Fe(CN)6]) at a suitable stoichiometric ratio, avoid byproducts or incomplete reactions, ensure the stability of the crystal morphology during the reaction, and generate a Prussian blue structure with good electrochemical activity. The mass ratio of the alkalized MXene nanosheets to the Prussian blue is 1:4~8. When the mass ratio exceeds 1:8, too much Prussian blue may accumulate on the surface of the sheet, hindering the transmission of electrons and ions, and reducing the electrochemical performance. If the Prussian blue loading is insufficient (less than 1:4), the functionality of the Prussian blue in the composite material is insufficient and the electrochemical activity cannot be significantly improved; the mass ratio of 1:4~8 can keep the Prussian blue evenly distributed on the surface of the MXene sheet, avoid block deposition and accumulation, and improve the stability and performance of the structure.

[0024] Preferably, in step S03, the mixing time is 4-5 hours, the centrifugal washing speed is 5000-6000 rpm, the centrifugal time is 3-5 minutes, and the number of centrifugal times is 7-10 times. Appropriate stirring time ensures that Prussian blue is evenly distributed on the surface of the MXene layer without agglomeration, thereby improving the structural uniformity and mechanical stability of the composite material. Multiple efficient washings can effectively remove impurities and reduce the side effects of impurities in long-term electrochemical reactions, such as material structure destruction or reduced interface bonding caused by ion migration.

[0025] Preferably, a second object of the present invention is to provide a MXene / Prussian blue composite material prepared according to the above preparation method.

[0026] The beneficial effects of the present invention are: The present invention first alkalizes MXene to make Na + Intercalation expands the interlayer spacing of MXene, and the -F group is replaced by the -OH group. After the alkali induction process, a 3D interconnected wrinkled structure is obtained, which promotes ion transport. MXene nanosheets, as a support for the growth of Prussian blue, can inhibit the accumulation and agglomeration of Prussian blue nanoparticles, thereby improving the effective utilization rate of Prussian blue. At the same time, due to the rapid generation of Prussian blue, many defects are generated. While increasing the transmission speed of cations, the conductivity of Prussian blue is also improved, thereby improving the electrochemical performance of the material.

[0027] Due to the synergistic effect of MXene and Prussian blue, the composite material exhibits high specific capacitance, excellent rate performance and cycle stability; the method has mild reaction conditions and high reaction efficiency, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 This is the XRD pattern of the MXene / Prussian blue composite material synthesized in Example 1 of the present invention.

[0030] Figure 2 The figure is a comparison of the rate performances of Example 2 of the present invention and Comparative Examples 1 and 2 obtained according to the CV curves.

[0031] Figure 3 The figure is a comparison of the rate performances of Example 2 of the present invention and Comparative Examples 1 and 2 obtained according to the GCD curves. DETAILED DESCRIPTION

[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0033] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] Example 1 A MXene / Prussian blue composite material and a preparation method thereof are as follows: S01: First, slowly add 1g LiF into 20ml HCl (9M) solution, then slowly add 1g Ti3AlC2, and react for 48h at 290rpm and 40℃ oil bath conditions. The product after the reaction was first centrifuged at 3500rpm with 8ml 12.1M HCl for 5min, washed twice by centrifugation, and then washed with deionized water, the speed was changed from 3500rpm to 6000rpm, increasing by 500rpm each time, and centrifuged for 5min each time. Centrifuge until the pH of the upper clear liquid is neutral, stir and ultrasonicate the solution in an ice bath under N2 atmosphere for 2h, then centrifuge at 3500rpm for 40min, take the upper suspension, put it into a cold dryer for drying, and collect it to obtain lamellar MXene nanosheets.

[0035] S02: 100 mg of MXene nanosheets were placed in 100 ml of NaOH (1 M concentration) solution, heated and stirred in an oil bath at 80 °C for 1 h. Centrifuged and washed several times at 5000 rpm, each time for 4 min. When the upper clear liquid was neutral, it was placed in a vacuum tube drying oven at 60 °C and dried for 12 h.

[0036] S03: Put MXene nanosheets into deionized water with a concentration of 4 mg / ml, stir and sonicate in an ice bath under N2 atmosphere for 2 h, add 20 ml of 1 mmol CuSO4·5H2O into 10 ml of MXene solution, mix, slowly add 20 ml of 0.5 mmol K3Fe(CN)6 and mix for 4 h, centrifuge and wash several times at 6000 rpm, 3 min each time, until the supernatant is neutral, put it into a vacuum drying oven at 60°C and dry it for 12 h.

[0037] Example 2 A MXene / Prussian blue composite material and a preparation method thereof are as follows: S01: First, slowly add 1g LiF into 20ml HCl (9M) solution, then slowly add 1g Ti3AlC2, and react for 48h at 290rpm and 40℃ oil bath conditions. The product after the reaction was first centrifuged at 3500rpm with 8ml 12.1M HCl for 5min, washed twice by centrifugation, and then washed with deionized water, the speed was changed from 3500rpm to 6000rpm, increasing by 500rpm each time, and centrifuged for 5min each time. Centrifuge until the pH of the upper clear liquid is neutral, stir and ultrasonicate the solution in an ice bath under N2 atmosphere for 2h, then centrifuge at 3500rpm for 40min, take the upper suspension, put it into a cold dryer for drying, and collect it to obtain lamellar MXene nanosheets.

[0038] S02: 100 mg of MXene nanosheets were placed in 100 ml of NaOH (1 M concentration) solution, heated and stirred in an oil bath at 80 °C for 1 h. Centrifuged and washed several times at 5000 rpm, each time for 4 min. When the upper clear liquid was neutral, it was placed in a vacuum tube drying oven at 60 °C and dried for 12 h.

[0039] S03: Put MXene nanosheets into deionized water with a concentration of 4 mg / ml, stir and ultrasonicate in an ice bath under N2 atmosphere for 2 h, add 20 ml 1.5 mmol CuSO4·5H2O into 10 ml MXene solution, mix, slowly add 20 ml 0.75 mmol K3Fe(CN)6 and mix for 4 h, wash by centrifugation at 6000 rpm for several times, 3 min each time, put into a vacuum drying oven at 60°C and dry for 12 h.

[0040] Comparative Example 1 The MXene preparation method is as follows: S01: First, slowly add 1g LiF into 20ml HCl (9M) solution, then slowly add 1g Ti3AlC2, and react for 48h at 290rpm and 40℃ oil bath conditions. The product after the reaction was first centrifuged at 3500rpm with 8ml 12.1M HCl for 5min, washed twice by centrifugation, and then washed with deionized water, the speed was changed from 3500rpm to 6000rpm, increasing by 500rpm each time, and centrifuged for 5min each time. Centrifuge until the pH of the upper clear liquid is neutral, stir and ultrasonicate the solution in an ice bath under N2 atmosphere for 2h, then centrifuge at 3500rpm for 40min, take the upper suspension, put it into a cold dryer for drying, and collect it to obtain lamellar MXene nanosheets.

[0041] Comparative Example 2 The preparation method of Prussian blue is as follows: S01: Dissolve 2.5g CuSO4·5H2O in 50ml deionized water, dissolve 1.65g K3Fe(CN)6 in 50ml deionized water, slowly drop the CuSO4·5H2O solution into K3Fe(CN)6, stir magnetically for 6h, centrifuge and wash several times at 6000rpm, each time for 3min, put into a forced air drying oven at 60℃ and dry for 12h.

[0042] Test Data Using Example 1-2 and Comparative Example 1-2 as working electrodes, activated carbon as counter electrode, Ag / AgCl as reference electrode, and 10M LiTFSI as electrolyte, three electrodes were assembled and CV and GCD were tested using an electrochemical workstation (Shanghai CHI660E).

[0043] from Figure 1 It can be concluded that MXene and Prussian blue are successfully composited.

[0044] from Figure 2 to Figure 3 It can be seen that the voltage window of the composite material becomes wider and the impedance is smaller under the electrolyte of high salt concentration.

[0045] from Figure 2 and Figure 3 It can be concluded that the specific capacity of Example 2 at 1 mV / s is 519 F / g, and at 0.5 A / g, the specific capacity is 523 F / g, while the specific capacity of Comparative Example 1 at 1 mV / s is 165 F / g, and at 0.5 A / g, the specific capacity is 173 F / g, and the specific capacity of Comparative Example 2 at 1 mV / s is 266 F / g, and at 0.5 A / g, the specific capacity is 237 F / g. Figure 2 and Figure 3 It can be seen that the MXene / Prussian blue composite material prepared by the present invention can obtain a higher specific capacitance, and the electrode material used for supercapacitors can improve its performance.

[0046] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a MXene composite material for a supercapacitor, characterized in that: The following steps are involved: S01: Preparation of MXene nanosheets: deionized water and HCl are stirred and mixed to obtain a mixed acid solution; LiF and Ti3AlC2 powders are slowly added to the mixed acid solution in sequence and stirred evenly, and then transferred to an oil bath for heating, stirring and etching; after the etching is completed, the precipitate is centrifugally washed with HCl and deionized water in sequence until the pH of the supernatant is neutral; the precipitate is placed in an ultrasonic crusher and ultrasonicated with protective gas, and then placed in a centrifuge for centrifugation to obtain the upper suspension and place it in a cold dryer for cold drying; S02: Place the MXene nanosheets in a NaOH solution, stir and heat in an oil bath, centrifuge and wash, and then dry in a vacuum drying oven; S03: The alkalized MXene nanosheets are mixed with CuSO4·5H2O and K3Fe(CN)6, stirred, centrifuged and washed, and dried in a vacuum drying oven to obtain a MXene / Prussian blue composite material.

2. The method for preparing a MXene composite material for a supercapacitor according to claim 1, characterized in that: In step S01, in the mixed acid solution, the volume ratio of the deionized water to the HCl is 1:2.9-3.1; the mass ratio of the LiF to the Ti3AlC2 is 1:1-1.

2.

3. The method for preparing a MXene composite material for a supercapacitor according to claim 1, characterized in that: In step S01, when transferring to an oil bath for heating, stirring and etching, the heating time of the oil bath is 48-52 hours and the heating temperature is 38-42°C.

4. The method for preparing a MXene composite material for a supercapacitor according to claim 1, characterized in that: In step S01, the precipitate obtained after etching is first centrifugally washed twice with HCl, and then centrifugally washed with deionized water until the pH of the supernatant is neutral; when using HCl for centrifugal washing, the volume of HCl is 3~5mL; the centrifugal speed is 3000~4000rpm; the centrifugal time is 3~5min; when using deionized water for centrifugal washing, the centrifugal speed is 3500~6000rpm; the centrifugal time is 4~6min; the number of centrifugation is 7~10 times.

5. The method for preparing a MXene composite material for a supercapacitor according to claim 1, characterized in that: In step S01, the precipitate is placed in an ultrasonic crusher and ultrasonicated with protective gas for 2 to 2.5 hours, and then placed in a centrifuge. After centrifugation at a speed of 3500 to 4000 rpm for 40 to 50 minutes, the upper suspension is taken and placed in a cold dryer for cold drying.

6. The method for preparing a MXene composite material for a supercapacitor according to claim 1, characterized in that: In step S02, the concentration of the NaOH solution is 0.9-1.2 mol / l; the temperature of the oil bath is 60-80°C, and the heating time is 1-1.5h.

7. The method for preparing a MXene composite material for a supercapacitor according to claim 1, characterized in that: In step S02, during centrifugal washing, the centrifugal speed is 5000-6000 rpm, the centrifugal time is 3-5 min, and the number of centrifugal times is 7-10 times; then it is placed in a vacuum drying oven, the drying temperature is 40-60°C, and the drying time is 10-12 hours.

8. The method for preparing a MXene composite material for a supercapacitor according to claim 1, characterized in that: In step S03, the molar ratio of the CuSO4·5H2O to the K3Fe(CN)6 is 2:1, and the mass ratio of the alkalized MXene nanosheets to the Prussian blue is 1:4-8.

9. The method for preparing a MXene composite material for a supercapacitor according to claim 1, characterized in that: In step S03, the mixing and stirring time is 4 to 5 hours, the centrifugal washing speed is 5000 to 6000 rpm, the centrifugal time is 3 to 5 minutes, and the number of centrifugation times is 7 to 10 times.

10. The MXene composite material for supercapacitor prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The MXene composite material for supercapacitors is a MXene / Prussian blue composite material.

Citation Information

Patent Citations

  • PB compound nanomaterial as well as preparation method and application thereof

    CN109675608A

  • Prussian blue analog / MXene composite electrode material and in-situ preparation method and application thereof

    CN110783536A

  • Self-supporting negative electrode material and preparation method thereof, negative electrode plate and secondary battery

    CN114914427A

Cited By

  • High-heat electrical gel with anisotropic structure as well as preparation method and application of high-heat electrical gel

    CN120699313A

  • High-thermoelectricity gel of anisotropic structure, and preparation method and application thereof

    CN120699313B